Passwords philology, security, authentication - Lennon, Brian, 1971- (The Belknap Press of Harvard University Press, 2018)
Today we regard cryptology, the technical science of ciphers and codes, and philology, the humanistic study of human languages, as separate domains of activity. But the contiguity of these two domains is a historical fact with an institutional history. From the earliest documented techniques for the statistical analysis of text to the computational philology of early twenty-first-century digital humanities, what Brian Lennon calls "crypto-philology" has flourished alongside, and sometimes directly served, imperial nationalism and war. Lennon argues that while computing's humanistic applications are as historically important as its mathematical and technical origins, they are no less marked by the priorities of institutions devoted to signals intelligence. The convergence of philology with cryptology, Lennon suggests, is embodied in the password, an artifact of the linguistic history of computing that each of us uses every day to secure access to personal data and other resources. The password is a site where philology and cryptology, and their contiguous histories, meet in everyday life, as the natural-language dictionary becomes an instrument of the hacker's exploit.--